Flow control : theoretical concept of absolute instability - Oertel, Herbert (KIT Scientific Publishing, 2010)
At the 37th Prandtl memorial lecture on Regions of Viccous Flow, H.Oertel 1994 developed for the first time the stability theory of local perturbations in boundary layers and wake flows, as well as their practical application in the flow control of vehicle flows and the boundary layer of civil aircraft wings.This work presents how the stability theory concept of absolute instability has advanced and proven in practice in the last 15 years in terms of the efficient flow control.